PENGGUNAAN MODEL RESOUCE BASED LEARNING (RBL) DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS V SD NEGERI 1 WONOKROMO TAHUN AJARAN 2014/2015 - finanda, wiwit (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Implementation Of Resouce Based Learning (RBL) Model In Improving Social Science Learning For The Fifth Grade Students Of SD Negeri 1 Wonokromo In The Academic Year Of 2014/2015. The purpose of this research is to improve social science learning for the fifth grade students by implementing resouce based learning model. This research is collaborative classroom action research, the steps are planning, implementation, observation, and reflection. The subject of this research is fifth grader amounted to 21 students. The collecting data through observation, interview, documentation and test. The results of this study can improve the process and learning outcome. The Conclusion of research is the implementation of resouce based learning model can improve social science learning for the fifth grade students of SD Negeri 1 Wonokromo in the academic year of 2014/2015. . Keywords: resource based learning, learning improvement, social science Abstrak: Penggunaan Model Resouce Based Learning (RBL) dalam Peningkatan Pembelajaran Pada Siswa Kelas V SD Negeri 1 Wonokromo Tahun Ajaran 2014/2015. Tujuan penelitian ini untuk meningkatkan pembelajaran IPS pada siswa kelas V dengan menggunakan model Resouce Based Learning (RBL). Penelitian ini merupakan penelitian tindakan kelas kolaboratif, tahapannya perencanaan, pelaksanaan, observasi, refleksi. Subjek penelitian siswa kelas V berjumlah 21 siswa. Pengumpulan data dengan observasi, wawancara, dokumentasi dan tes. Hasil penelitian menunjukkan bahwa ada peningkatan pembelajaran IPS siswa menggunakan model RBL. Kesimpulan penelitian yaitu penggunaan model pembelajaran resouce based learning dapat meningkatkan pembelajaran IPS pada siswa kelas V SD Negeri 1 Wonokromo Tahun Ajaran 2014/2015. Kata Kunci: resouce based learning, peningkatan pembelajaran, IPS